HUBUNGAN PENGETAHUAN, SIKAP DAN USIA DOKTER TERHADAP KELENGKAPAN PENGISIAN BERKAS REKAM MEDIS PADA PASIEN BPJS DI RUMAH SAKIT AISYIYAH BOJONEGORO - Rosita Ramadhani Kumalasari; Yudhy Dharmawan; Sri Winarni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The number of incomplete medical record files at RS.Aisyiyah Bojonegoro during 2015 is still high and need to resolve.In theoretical there are various factors that affect the incompleteness of the medical record file, that is knowledge and attitude factor.This research is designed in a cross sectional which aims to identify the characteristics of doctors , analyzing the performance of doctors in the completeness of the filing records, and analyzing the predisposing, enabling and strengthening factors affecting the completeness of the medical records file. The next step is to develop a strategic plan to reduce the incomplete number of medical record files.From the research, it is found that the variables that become the enabling factor in increasing the number of file medical record are commitment, awareness, obedience, and motivation of the physician While the obstacles are non compliance to SPO, poor job design, work environment and less support facilities , as well as low support from peers and managerial.Based on the research, general conclusions can be drawn from the study, among others, to reduce inhibiting factors, among others by developing a good working environment and supporting facilities, developing job design and increasing doctors commitment, maintaining and improving doctor's knowledge by supervise method, re-socialization and training filling out medical record files as well as safeguarding and enhancing doctors' commitment by providing a fair reward system.